IMPLEMENTASI NHT BERBASIS CULTURALLY RESPONSITIVE TEACHING UNTUK MEMOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Vannesa Almayra Nugroho; Sari Yustiana; Muhamad Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Kurikulum Merdeka emphasizes learning that is relevant to the characteristics, needs, and culture of students. However, the results of observations in class 5 of SDN Kalisari 1 Sayung, Demak showed that learning was still conventional and did not integrate the culture of students. This triggers a lack of student learning motivation. This study aims to determine the implementation of Numbered Heads Together (NHT) based on Culturally Responsive Teaching (CRT) to motivate student learning in elementary schools. This study uses a qualitative descriptive case study type. Data were collected through observation, interviews, and documentation. Data reduction, presentation, and drawing conclusions. The results of this study Numbered Heads Together (NHT) based on Culturally Responsive Teaching (CRT) is able to overcome conventional and monotonous learning problems into learning that is more enjoyable, meaningful, and integrated with the culture of students. In addition, learning with Numbered Heads Together (NHT) based on Culturally Responsive Teaching (CRT) can motivate student learning as indicated by activeness in learning, involvement in group discussions, confidence in their abilities, perseverance in doing assignments, and not giving up easily when facing difficulties.